Barbed Wire in Aphrodite’s Garden - Bandler, John (Bandler Corporation, 2010)
Cyprus, 1955-1957. Love and courage collide with bigotry, decadence, and revolution in ethnically divided Cyprus as British control crumbles. A schoolboy battles his mantle of cowardice, a tycoon’s son rebels against his heritage, and a young womanizer seeks redemption as a guerrilla-assassin.
Context: Barbed Wire in Aphrodite’s Garden by John Bandler is a novel set in Cyprus in 1955 to 1957 against the guerrilla conflict involving Greek and Turkish Cypriots (as well as Greece and Turkey), and the British occupiers. The island remains divided. The time intersects that of Lawrence Durrell’s Bitter Lemons, and likely Durrell’s writing of The Alexandria Quartet. In 2006, in a session on creative influences, the author John Bandler presented “Bitter Lemons and Barbed Wire” to the biennial International Lawrence Durrell Conference. In 2007, Bandler spoke on “Durrell’s Cyprus—Tainted Observations on the Colonial and Postcolonial” at the ACLALS Conference: Literature for Our Times. See also http://www.bandler.com/venus
Keywords: EOKA; TMT; MI6; Volkan; Makarios; Grivas; Dhigenis; Cyprus; Greece; Turkey; Britain; colonialism; terrorism; terrorist; loyalty; ethnic strife; revenge; betrayal; teenage love; guerrilla